Komunikasi Kreatif Kelompok Informasi Masyarakat (KIM) dalam Mendorong Keterbukaan Informasi Menuju Desa Mendunia - Dewi, Eriyanti Nurmala (ArtComm, 2024)
This research examines the creative communication carried out by the Tarumajaya Smart Community Information Group (KIM) in encouraging information openness in Tarumajaya Village, Kertasari District, Bandung Regency towards becoming a global village. Research was conducted to find out how creative communication from Graham Wallace (1926) which included preparation, incubator, illumination and verification was used by KIM Smart Tarumajaya as a representation of community organizations with the people of Tarumajaya Village and with Tarumajaya Village officials. KIM is an acronym for the Community Information Group which was formed by the community, from the community, for the community to independently and creatively manage information and empower the community in order to increase the added value of their region. This research uses a qualitative method with a case study approach. Data collection techniques were carried out by conducting interviews, observation and documentation. The research results show that the creative process of KIM Smart Tarumajaya was carried out through four stages, namely preparation, incubator, illumination and verification. The results are communicated by referring to the principle of the village, by the village, for the village using digital platforms such as websites, podcasts, YouTube, Instagram and Facebook which penetrate the boundaries of space and time to become a global village.